Design of an Acoustic Bender Transducer for Active Sonobuoys - Pyo, Seonghun (Sensors (Basel), 2019)
Recent underwater vehicles can operate with a much lower level of noise, which increases the need for an active sonobuoy with a high detection performance. These active sonobuoys mainly use bender transducers as a projector that emits sound waves. In this study, we designed a high-performance bender transducer and verified the validity of the design through experiments. For this purpose, first we analyzed the variation of the peak transmitting voltage response (TVR) level and peak TVR frequency of the bender transducer, in relation to its structural parameters. The performance of the bender transducer was analyzed using the finite element method. Then we derived the optimal structure of the bender transducer to achieve the highest TVR. Based on the design, a prototype of the bender transducer was fabricated and its acoustic properties were measured to confirm the validity of the design.